En busca de espacios y en busca de aliados la gerra del pacífico vista a través del diario oficial El Peruano ( la defensa de Lima y la resistencia serrana) - Rosario, Emilio (2005)
This article has the purpose of showing the importance of the «El Peruano» newspaper to generate a trend of public opinion in favor of the Peruvian government during a dramatic period as «the war against Chile». The official newspaper by publishing its editorial notes, legislative and executive messages and decrees portrayed like it wants, and did not like the reality was in the context of southern operations. The objective of these actions was cheering local population up. This time, the temporary frame lasted from the occupation of Lima are occupation Arequipa when temporally El Peruano stopped circulating the war.